The Effect Of Health Service Quality On Patient Satisfaction At Bangkirai Pratama Clinic, Pt. Pamapersada Nusantara Distrik Smms, Central Kalimantan - Bendra Krestopri; Sumeidi Kadarisman; Taufan Nugroho; Kosasih Kosasih; Etty Sofia Mariati Asnar (Publikasi Indonesia, 2025)
Quality of health services is a health service provided in accordance with standards to patients by health agencies with the wishes of patients can be fulfilled. Patient satisfaction is an assessment of health services that a person feels after health workers perform health services in accordance with expectations or not in accordance with expectations. This study aims to examine the effect of health service quality consisting of aspects of reliability, responsiveness, assurance, empathy & tangible assessment on patient satisfaction at the Pratama Bangkirai clinic. This research was conducted on 19 May - 01 June, 2025. This type of quantitative research uses descriptive and verification methods. The variable to be studied is the quality of health services consisting of the five aspects as independent variables and the level of patient satisfaction as the dependent variable. The population in this study was 1400 patients and a sample of 93 respondents using the slovin formula. Data collection techniques by conducting direct surveys and distributing google form questionnaires. Instrument tests use validity tests, reliability tests and classical assumption tests. The statistical analysis design in this study is descriptive analysis, verification analysis (multiple linear regression). Hypothesis testing using a partial significance test (T-test), simultaneous hypothesis testing (F-test), correlation analysis of the coefficient of determination. The results showed that all variables consisting of health service quality (reliability, responsiveness, assurance, empathy & tangible) had a simultaneous effect on patient satisfaction with an Fcount value (52.618) which was greater than the Ftable for d (f) for n of